PELATIHAN VIRTUAL LOCAL AREA NETWORK (VLAN) DAN ROUTING DI SEKOLAH SMK TUNAS MUDA BERKARYA - Sitohang, Sunarsan; Pangaribuan, Hotma; Sirait, Ganda (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2024)
Technological developments have a huge impact on the world of education. Today's advanced technology is very helpful for humans in doing their work, so it must be applied to get its benefits. Virtual Local Area Network (VLAN) is network technology in the logical grouping of users and equipment connected to the network connected to administratively defined ports on a switch regardless of the location of the switch is placed. With VLANs, a Local Area Network (LAN) can be divided into several different segments. VLANs also allow for the consolidation of networks that are physically separate, but as if they were in the same segment. The main aim of this training is to create students who can apply VLAN and Routing technologies to make it easier to do network-related work and understand how to use it. After the service was carried out, the knowledge of students is increasing, marked by the results of the evaluation that is carried out at the end of each service session in each material topic. The improvement of students' understanding also increased in router and VLAN configurations, characterized by the ability of students to do configuration exercises without assistance from service members. From this service activity, it can be concluded that the service went smoothly, and the students' knowledge became more about routing and VLAN.